Commercial aviation safety - Rodrigues, Clarence C.; Cusick, Stephen K.; Wells, Alexander T. (New York, NY : McGraw-Hill Professional, 2012)
'Presenting current practice and procedures from all major air traffic and regulatory agencies, this book covers the entire commercial aviation safety system--from human safety to accident investigation. Commercial Aviation Safety, Fifth Edition greatly expands the focus of the Fourth Edition to include the international and Safety Management Systems (SMS) knowledge required by today's aviation safety professional. Most aviation safety-related texts cover only issues related to the FAA and NTSB. However, as a practicing professional in the aviation field, one must also be knowledgeable about ICAO, SMS, OSHA, and EPA. This book delivers on this need. Offering a comprehensive analysis on the entire aviation safety system, this authoritative guide provides a broad understanding of aviation safety for students entering the field, and serves as a handy reference for the practicing aviation safety professional.Commercial Aviation Safety, Fifth Edition: Now includes International Civil Aviation Organization (ICAO) regulations Provides organization and rule-making process of all four relevant regulatory agencies in one place Contains expanded accident causation models Features new research on human factors in aviation safety Offers new information on air traffic control and aircraft safety systems Includes updated airport and airline safety information Contains a new chapter on Safety Management Systems (SMS) Provides knowledge on hot-button safety topics like runway incursions and security Student learning features: Chapter outlines with each major topic covered Chapter objectives after the outline Heavily illustrated with tables, figures, and exhibits Key terms--each chapter ends with a listing of key terms used in the text Review questions at the end of each chapter cover all the important points A listing of suggested readings included after each chapter'--
'Presenting current practice and procedures from all major air traffic and regulatory agencies, this book covers the entire commercial aviation safety system--from human safety to accident investigation'--
Rev. ed. of: Commercial aviation safety / Alexander T. Wells. 2003.
Includes bibliographical references and index.
Keywords: Aeronautics -- United States -- Safety measures; Aeronautics, Commercial -- United States -- Safety measures